POLA KOMUNIKASI KELOMPOK ASALVO AUTO COMMUNITY PEKANBARU DALAM MEMBANGUN KOHESIVITAS UNTUK PERKEMBANGAN OTOMOTIF DI PEKANBARU - Ramadhan, Firas Surya; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Various kinds of automated communities exist in Indonesia, one of them is the Originvo Auto Community which has been widely spread in various regions in Indonesia such as one in the city of Pekanbaru with the name of the Originvo Auto Community Pekanbaru. Asalvo Auto Community Pekanbaru carries out forms of interaction and communication to increase its existence in the world of homeland modification, solidarity between members, and very close cohesiveness within the community. This study aims to determine the communication patterns and factors that influence the form and communication network of the Originvo Auto Community Pekanbaru in building cohesiveness for automotive development in Pekanbaru. Group communication occurs when three or more people face to face, usually under the direction of a leader to achieve a common goal or goal and influence one another. This research uses descriptive qualitative research method, which has selected six selected informants, namely a community leader, two administrators, and three members of the Originvo Auto Community Pekanbaru. The results of this study indicate that Asalvo Auto Community Pekanbaru conducts face-to-face communication and virtual communication where communication and interaction can occur with anyone, anytime, and anywhere. Communication is two-way and the communication network formed in the form of a scheme of all channels. In interacting this community uses symbols in the form of everyday language in the community. Cooperation in this community is more dominant than competition, this community has a written code of ethics that is used as norms and rules, this community always chooses and creates the right atmosphere in carrying out activities in order to create a sense of comfort and conducive. From the communication patterns and factors that affect the effectiveness of this communication form the cohesiveness of the Originvo Auto Community Pekanbaru among fellow members. Keywords: Communication Group, Asalvo Auto Community